TNF and MAP kinase signaling pathways - Sabio, Guadalupe (2014)
The binding of tumor necrosis factor α (TNFα) to cell surface receptors engages multiple signal transduction pathways, including three groups of mitogen-activated protein (MAP) kinases: extracellular-signal-regulated kinases (ERKs); the cJun NH(2)-terminal kinases (JNKs); and the p38 MAP kinases. These MAP kinase signalling pathways induce a secondary response by increasing the expression of several inflammatory cytokines (including TNFα) that contribute to the biological activity of TNFα. MAP kinases therefore function both upstream and down-stream of signalling by TNFα receptors. Here we review mechanisms that mediate these actions of MAP kinases during the response to TNFα.